Dracoleuctra, a new wingless stonefly genus from southern Oregon, U.S.A. (Plecoptera: Leuctridae) - Lee, Jonathan J.; Baumann, Richard W. (Zootaxa, 2022)
Dracoleuctra siskiyou Lee & Baumann gen. nov. sp. nov. a new apterous genus and species in the stonefly family Leuctridae (Insecta, Plecoptera), is described from males and females collected in southern Oregon, U.S.A. Habitus and terminalia are illustrated using both light photography images and scanning electron micrographs. Diagnostic characters, habitat, biological notes, and stonefly apterism in the Klamath Mountains region are discussed.